Determinants of regional distribution of AKP votes: Analysis of post-2002 parliamentary elections - DENİZ, PINAR (WILEY, 2021)
Electoral politics and regional variation in socio-economic conditions of individuals receive huge interest in countries with sizable political tension. Even though Turkey has undergone a combination of periods of economic success and a period of economic and political turmoil, it has been governed by a single political party during the last two decades-Adalet ve Kalkinma Partisi (AKP)- Justice and Development Party. This paper examines the determinants of the variation in regional vote shares of AKP between the 2002 and 2018 parliamentary elections using panel data estimation method-effects-which allows us to account for time invariant region-specific unobserved fixed effects. Our findings demonstrate that inflation, unemployment, per capita GDP growth, provision of healthcare, industrial sector growth rates, change in the ageing of the population and rate of absenteeism (voter turnout) are essential factors in voters' decisions. Our additional results reveal that the effects of socio-economic factors on the AKP vote shares were distinctly different for the AKP stronghold provinces and the eastern regions that are mostly populated with Kurdish, suggesting that ideological position of the voters also play an essential role in voters' response to the changes in socio-economic conditions.
Keywords: AKP; regional distribution; Turkey; voting behaviour